Efektivitas Program Tahfidzul Qur’an dalam Pengembangan Karakter Qur’ani - Fenty Sulastini; Moh. Zamili (Jurnal Pendidikan Islam Indonesia, 2019)
The objectives of this research are implementation of the Tahfidzul Qur'an Program, characteristics of students who have taken tahfidzul qur'an program and effectiveness of tahfidzul qur'an program in developing qur'ani character. The conclusion of this research is the students’ qur'ani character will be easily created by memorizing the Qur'an because students must have a good akhlak to maintain their memorization of the Qur’an. Tahfidzul qur'an program is an effective action in developing the Qur'ani character of the students at SMP Daarul Qur’an. It starts with making a habit of memorizing the Qur'an to create a character of the Qur'an in them. This research used qualitative perspective to examine the context of research. Data collection in this research carried out by observations, documentation, and interviews.